Analysis of Problems and Countermeasures in the Promotion of New Energy Vehicles in China - Bi, Chunkai; Li, Guanru (Transactions on Economics, Business and Management Research, 2024)
At present, China's new energy vehicle industry is in the stage of rapid development, but it also faces a series of challenges. These include problems in the installation of community charging facilities and home charging stations, negative public opinion on new energy vehicles on the Internet, restrictions on the supply of key materials for new energy batteries, and a global shortage of chips. To overcome these constraints, society needs to adopt diversified strategic measures. Policy promotion is the key. Relevant policies can guide the property management of residential communities and improve the community power grid capacity, so as to promote the rapid construction of shared EV charging facilities. At the same time, society also needs to increase the publicity of the network platform and improve the public's cognition and understanding of new energy vehicles, so as to change the inherent concept of consumers. In addition, industry leaders should be actively encouraged to accelerate technology research and development in order to break through the existing technical bottlenecks. Through these comprehensive measures, people can effectively promote the sustainable and healthy development of the new energy vehicle industry.